Frequency of Recurrent Wheeze in Breastfeeding Children Presenting to Rehman Medical Institute Peshawar - Munaza Naeem (Indus Journal of Bioscience Research, 2025)
Introduction: Recurrent wheeze in children is a significant health issue, often linked to respiratory infections and environmental exposures. Breastfeeding, known for its immunological benefits, has been associated with reduced respiratory morbidity. However, limited data exist on the protective role of breastfeeding against recurrent wheeze in children in Pakistan. This study focuses on determining the frequency of recurrent wheeze in breastfeeding children and its associated factors. Objectives: To determine the frequency of recurrent wheeze in breastfeeding children aged 1 to 5 years presenting to Rehman Medical Institute, Peshawar. Materials and Methods: This cross-sectional study was conducted from 1st June 2024 to 30th November 2024 at the Pediatric Department, Rehman Medical Institute, Peshawar. A total of 217 children aged 1–5 years with a history of exclusive breastfeeding were enrolled. Data were collected through interviews and analyzed using SPSS version 22. Results: Recurrent wheeze was observed in 16.1% of children. Exclusive breastfeeding significantly reduced the prevalence of recurrent wheeze compared to partial breastfeeding (p < 0.05). Conclusion: Exclusive breastfeeding plays a protective role against recurrent wheeze in young children and should be encouraged to improve respiratory health.